Effectiveness of Antiretroviral Therapy among HIV-Infected Prisoners and some related factors at Tan Lap prison, Phu Tho 2018 - 2020 (Vietnam Journal of Community Medicine, 2021)
Objectives: To describe the responses to Antiretroviral Therapy (ART) among HIV-infected prisoners and some related factors at Tan Lap Prison, Phu Tho. Methods: A retrospective, cross-sectional descriptive study was conducted on 270 HIV-infected prisoners who were receiving antiretroviral therapy. Results: The response rate to ART in 2018, 2019 and 2020 was 93.7%, 95.9% and 94.4%, respectively. There was no difference in the response rate to ART between men and women. In 2020, the rate of adherence to ART achieved 94.1% with good compliance; 52.2% of patients reported adequate knowledge about ART. There is a strong relationship between adherence and response to ART with OR = 83 (95%CI: 21.63 - 318.46). Other factors such as patient's knowledge, hepatitis co-infection status, transmission route, ethnicity, etc were not associated with response to ART. Conclusion: The response rate to ART of patients over 2018, 2019, 2020 is high. The response to ART of patients showed a significant difference statistically with adherence to ART.
Keywords: Antiretroviral therapy (ART), prisoners, HIV infections.